Supply Estimates 1971-72: Class VI Environmental Services - Her Majesty's Stationary Office (HMSO, 1971)
ESTIMATE of the amount required in the year ending 31 March 1972 for the salaries and expenses of the Department of the Environment, and certain Tribunals Commissions, Committees, &c . . and for expenditure on the collection of motor vehicle duties, &c. and the registration of motor vehicles in Great Britain
ERAF: A6 SE 1971-72(6)
Keywords: Supply Estimates; 1971-72; Class VI; Environmental Services